Responsibilities of Issuers and Investment Managers in Mutual Fund Default Cases: Case Study of PT Tridomain Performance Materials Tbk (Journal of Civil Criminal Law, 2025)
The capital market is one of them part important in representation condition country's economy. In the capital market there are several instruments are traded, one of which is is mutual funds. Mutual funds become enough choice​ interesting for society, however there is case fail pay that mutual fund investors experience​ loss. Case fail pay product mutual funds viz fail pay consequential RDT assets debt securities issued by PT. Tridomain Performance Materials Tbk Study This use method approach juridical normative that is study law literature carried out with method research material References or secondary data as base For researched with method stage search to regulation legislation and related literature​ with the problems studied. And using secondary data as base For researched. Protection law can done with use protection law preventive and repressive in case investment mutual funds as form protection to investors from government. Losses experienced by investors as a result fail pay PT. TDPM to MMI, shows that TDPM has not quite enough answer as you can form pay whole obligations and compensation make a loss as well as accept all possible sanctions​ form administrative, civil, up to criminal. Protection law preventive can seen with exists regulation established legislation​ such as the Capital Markets Law, P2SK Law, POJK 48/2015, POJK 31/2015, and others. Protection law repressive form enforcement penalty from administrative even until bankruptcy. Not quite enough answer must carried out by TDPM viz pay obligation along with flower in accordance agreement debt restructuring up to imposition penalty. And necessary see form MMI's responsibility as Manager Invest in cases This.